Association between health literacy and body mass index among Iranian high school students - Tahereh Rahimi; Mahbubeh Barunizadeh; Dagfinn Aune; Fatemeh Rezaei (Scientific Reports, 2025)
Abstract The high prevalence of obesity and overweight in adolescence has become a global public health problem that increases the likelihood of chronic diseases in adulthood. Having a high level of health literacy is a key approach to reducing obesity-related risk factors and ensuring the health of adolescents in the future. The present study aims to assess the relationship between HL and body mass index (BMI) among Iranian high school students. This cross-sectional study was conducted on 500 high school students (250 boys and 250 girls) in Jahrom during January-May 2024. The samples were selected with a random cluster sampling method. Jahrom was divided into two clusters including north and south, and four high schools were randomly selected in each cluster. In each high school, a list of names for ninth, tenth, and eleventh grade students was extracted and students were selected randomly from each grade. Health Literacy Measure for Adolescents (HELMA) was used to evaluate HL. In addition, multivariate ordinal logistic regression analysis was utilized to determine the relationship between BMI and HL. The analysis was performed with SPSS version 23 and STATA version 14 software. A significance level of < 0.05 was considered in this study. The average age of the students was 16.4 ± 0.94 years and the average HL score was 61.9 ± 20.5. The average HL score among girls was significantly higher than among boys (64.6 ± 19.7 vs. 59.3 ± 21.1). Further, the average HL score among the students of the experimental science was higher than that among the humanities and mathematics ones. Totally, the HL among the students was inadequate (28.6%), problematic (28.8%), sufficient (24.4%), and excellent (18.2%). A positive significant association was observed between HL and BMI. The odds of obesity (versus overweight and normal groups) among the students with inadequate HL was 2.1 times compared to those with sufficient/excellent HL. A positive significant association was reported between HL and BMI among high school students. Public health professionals should consistently incorporate educational interventions that focus on increasing health literacy into school health programs to prevent adolescent overweight and obesity.